INTRINSIC AND LAYER-INDUCED VERTICAL TRANSVERSE ISOTROPY - Bakulin A. (My University, 2003)
Anisotropy caused by fine layering is often considered responsible for the differences between velocities obtained in sonic-log and seismic experiments. Understanding the link between the two is critical, especially in the current era of most wells being (highly) deviated.